PERENCANAAN SISTEM PLAMBING DAN HIDRAN KEBAKARAN PADA PROYEK PEMBANGUNAN HOTEL PESONA ALAM - Ivana Patricia Lilipaly; Ririn Endah Badriani; Yeny Dhokhikah (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
Pesona Alam Hotel is one of the hotels located in the Cisarua area, Bogor. An adequate plumbing system and fire hydrant system planning are needed to support the Comfort and safety of hotel visitor activities. The Plumbing Tool Load Unit Method is used in determining the dimensions of both clean and wastewater. Isometric depiction of piping networks and determining the diameter of clean water pipes is assisted by Pipe Flow Expert software. Based on the calculation, it is found that the need for clean water per day at Pesona Alam Hotel is 230 m3/day with the required diameter of clean water pipes of 0.5", 0.75", 1", 1.25", and 2". The estimated wastewater produced is 207 m3/day with a diameter of 1.25", 1.5", 2", 2.5", 3" and 4" wastewater. Whereas for the fire hydrant system, 3 types of fire hydrants are used, namely the pillar hydrant, fire hose reel, and sprinkler. The need for clean water for fire fighting is 270 m3.